Serine protease from Indian Cobra venom: its anticoagulant property and effect on human fibrinogen. (2nd January 2022) - Neema, K. N.; Hamse Kameshwar, Vivek; Nafeesa, Zohara; Kumar, Divya; Babu Shubha, Priya; Nagendra Prasad, M. N.; Swamy, Shivananju Nanjunda
Abstract: An unusual low molecular weight serine protease ( Nn P28) has been purified from Indian Cobra ( Naja naja ) venom from the western region of the Indian sub-continent. We reported the purification and characterization of low molecular Nn P28, emphasizing its role on human fibrinogen and anticoagulant property. Nn P28 was purified using gel filtration column chromatography followed by ion exchange chromatography. Protein gel electrophoresis revealed its molecular weight ≈28 kDa. The exact molecular mass of Nn P28 was found to be 27.12 kDa by mass spectrometry, hydrolyzing casein specifically, inhibited by PMSF suggesting it has a serine protease. Nn P28 prolonged the clotting time of re-calcified human citrated plasma and activated partial thromboplastin time (APTT) exhibiting anticoagulant property. Nn P28 exhibited fibrinogenolytic activity. Thus, the present study demonstrates the presence of unusual low molecular weight serine protease, emphasizing its importance of region-specific Indian cobra species.